Synthesis and Electronic Properties of b-RbNd(MoO4)2 - Atuchin, V.V.; Bekenev, V.L.; Chimitova, O.D.; Molokeev, M.S.; Bazarov, B.G.; Bazarova, J.G.; Khyzhun, O.Y.; Lim, C.S. (Asian Journal of Chemistry, 2014)
The electronic structure of b-RbNd(MoO4)2 has been evaluated from experimental and theoretical points of view. For the molybdate, X-ray photoelectron valence-band spectra have been measured. The total and partial densities of states of the constituent atoms of b-RbNd(MoO4)2 have been calculated using the FP-LAPW method. The FP-LAPW data reveal that main contributors in the valence-band region of b-RbNd(MoO4)2 are the Rb 4p-, Nd 4f-, Mo 4d- and O 2p-like states.